1982
DOI: 10.1113/jphysiol.1982.sp014133
|View full text |Cite
|
Sign up to set email alerts
|

Trophic action of epidermal growth factor on the pancreas and gastroduodenal mucosa in rats.

Abstract: SUMMARY1. Epidermal growth factor (EGF) infused subcutaneously in a dose of 10 ,g/kg . h but not 1 jug/kg . h inhibited spontaneous gastric acid and pepsin secretion, whereas when given intragastrically in a dose of 10 jug/kg . h it failed to affect this secretion.2. EGF injected intraperitoneally at 8 h intervals for 24 h significantly stimulated DNA synthesis in the gastroduodenal mucosa and the pancreas, whereas when administered intragastrically it stimulated DNA synthesis only in the gastroduodenal mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(78 citation statements)
references
References 14 publications
2
76
0
Order By: Relevance
“…suppresses the immune response (39, inhibits gastric acid secretion (3), stimulates DNA synthesis (6,12,27,38) accelerates wound healing (3 1, 40),and causes angiogenesis in the avascular corneal stroma (1 5). In accordance with these effects, EGF and its receptors are present in various tissues in the fetus and adult (1, 4, 1 1, 14,30,33).…”
mentioning
confidence: 99%
“…suppresses the immune response (39, inhibits gastric acid secretion (3), stimulates DNA synthesis (6,12,27,38) accelerates wound healing (3 1, 40),and causes angiogenesis in the avascular corneal stroma (1 5). In accordance with these effects, EGF and its receptors are present in various tissues in the fetus and adult (1, 4, 1 1, 14,30,33).…”
mentioning
confidence: 99%
“…However, although parenteral administration of EGF stimulates intestinal growth and maturation in suckling rodents (3,63,70) and intraluminal administration of EGF stimulates a mucosal proliferative response in the small intestine of the adult rat (82), the effects of parenterally administered EGF on the intestine of adult rodents were equivocal (1,14,24,75). Our investigation showed that the intestines from duodenum to rectum have specific EGF binding at short intervals (3 and 6 min) after 125I-EGF injection, although the levels of binding were low.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while investigating the remarkable proliferative and differentiation patterns of the Ins-IFN-mouse, EGF and EGF-R were found to be upregulated (Arnush et al 1996). Indeed, EGF has previously been shown to modulate pancreatic growth (Dembinski et al 1982, Logsdon 1986, 1987, Marti et al 1989, Verme & Hootman 1990, Mangino et al 1992. For example, systemic administration of EGF resulted in the induction of pancreatic duct proliferation in pigs (Vinter-Jensen et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, EGF and transforming growth factor -1 (TGF -1) were able to induce ductal and endocrine cell development respectively (Sanvito et al 1994). While the ability of EGF to stimulate epithelial cell and fibroblast proliferation is well documented, it has also demonstrated mitogenic properties for pancreatic growth (Dembinski et al 1982, Logsdon 1986, 1987, Marti et al 1989, Verme & Hootman 1990, Mangino et al 1992. In addition, evidence exists linking the overexpression of EGF and its receptor to both chronic pancreatitis and malignant pancreatic growth (Barton et al 1991, Korc et al 1992, Yamanaka et al 1993, Friess et al 1996.…”
Section: Introductionmentioning
confidence: 99%